Induction of NETosis in ovine colostral PMN upon exposure to Neospora caninum tachyzoites - Demattio, Lukas; Conejeros, Ivan; Grob, Daniela; Gärtner, Ulrich; Taubert, Anja; Hermosilla, Carlos; Wehrend, Axel (Frontiers in Veterinary Science, 2023)
Colostrum is one of the most important factors influencing the health and development of mammalian neonates. It is well-established that leukocytes, including polymorphonuclear neutrophils (PMN), are able to migrate from the mother to the infant via colostrum uptake. Here, we study for first time the ability of ovine colostral-derived PMN to extrude neutrophil extracellular traps (NETs) against the abortive apicomplexan parasite Neospora caninum. Although this cell population plays a significant role in the transmission of maternal innate immunity to neonates, little is known on colostral PMN activities in sheep. However, this cell population is a significant source of transfer of maternal immunity to the neonate. Colostral PMN continue to exert immunological effects even after the transition into the colostrum. Aim of present study was to investigate extrusion of NETs by ovine colostral PMN exposed to the apicomplexan parasite N. caninum which is known to cause devastating reproductive disorders in cattle, small ruminants, wildlife animals and dogs. The present study is the first of its kind to demonstrate that ovine colostral PMN are capable of producing NETs after stimulation with vital N. caninum tachyzoites. Ovine colostrum-derived NETs were detected by chromatin staining and antibody-based immunofluorescence staining of NET-specific structures including neutrophil elastase (NE) and global histones (H1, H2A/H2B, H3, H4), as well as scanning electron microscopy (SEM) analysis.